2011
DOI: 10.1002/hlca.201100185
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Tetrahydropyrimidines and Pyrrolidines by a Multicomponent Reaction of Dialkyl Acetylenedicarboxylates (=Dialkyl But‐2‐ynedioates), Amines, and Formaldehyde in the Presence of Iodine as a Catalyst

Abstract: Iodine was explored as an efficient catalyst for the synthesis of tetrahydropyrimidines 4 and pyrrolidines 5 by a multicomponent reaction of dialkyl acetylenedicarboxylates (¼ dialkyl but-2-ynedioates) 1, amines 2, and HCHO 3 at room temperature (Scheme). When the molar ratios of these substrates were 1 : 2 : 4 and 1 : 1 : 4, tetrahydropyrimidines and pyrrolidines were formed, respectively. The products were obtained in high yields (73 -85%) within a short period of time (25 -35 min , and antifungal agents [6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…84,85 2.14 Synthesis of tetrahydropyrimidines, pyrrolidines, tetrasubstituted pyrroles and dihydro-2-oxypyrroles from dialkylacetylene dicarboxylate A short and simple synthesis of tetrahydropyrimidine 93 and pyrrolidine 94 derivatives were accomplished in good to excellent yields at room temperature by the reaction of dialkylacetylene dicarboxylate (DAAD) A, amines B, and formaldehyde C in the presence of molecular iodine at room temperature (Scheme 36). 86,87 Interestingly, when the molar ratios of A, B and C were 1 : 2 : 4 and 1 : 1 : 4, tetrahydropyrimidine 93 and pyrrolidines 94 respectively, were formed.…”
Section: Synthesis Of Quinazolinones and Quinazolin-4-amines From Isa...mentioning
confidence: 99%
“…84,85 2.14 Synthesis of tetrahydropyrimidines, pyrrolidines, tetrasubstituted pyrroles and dihydro-2-oxypyrroles from dialkylacetylene dicarboxylate A short and simple synthesis of tetrahydropyrimidine 93 and pyrrolidine 94 derivatives were accomplished in good to excellent yields at room temperature by the reaction of dialkylacetylene dicarboxylate (DAAD) A, amines B, and formaldehyde C in the presence of molecular iodine at room temperature (Scheme 36). 86,87 Interestingly, when the molar ratios of A, B and C were 1 : 2 : 4 and 1 : 1 : 4, tetrahydropyrimidine 93 and pyrrolidines 94 respectively, were formed.…”
Section: Synthesis Of Quinazolinones and Quinazolin-4-amines From Isa...mentioning
confidence: 99%
“…Also, Das et al described [21] a three-component reaction of nitroarenes, formaldehyde, and dialkylacetylenedicarboxylates for the synthesis of 1,3,4,5-tetrasubstituted 1,2,3,6-tetrahydropyrimidines using indium as catalyst in dilute aqueous HCl at room temperature. The authors further extended their work and reported a multicomponent synthesis of tetrahydropyrimidines employing iodine as catalyst [22]. However, the reported methods use only dimethyl acetylenedicarboxylate, produce 1,3-identically substituted derivatives, need acid catalysis or/are performed in ionic liquids.…”
Section: Introductionmentioning
confidence: 97%
“…Our literature survey at this stage revealed that there are some reports [18][19][20][21][22] on the synthesis of tetrahydropyrimidine derivatives containing an ester group in position 5. Khan and coworkers reported [18] the synthesis of substituted tetrahydropyrimidine and bis-tetrahydropyrimidine derivatives in good-to-excellent yields involving the reaction of dimethyl acetylenedicarboxylate, amines/diamines, and formaldehyde in the presence of (HClO 4 -SiO 2 ) as catalyst.…”
Section: Introductionmentioning
confidence: 98%
“…In one of those examples, Das and his group synthesised dioxopyrrolidines using HCl as catalyst . In addition, in another report, they synthesized the same products using I 2 . Again, in few reports, the exchange of the functional groups of the alkynoates with the solvents was observed whereas, in some cases, the solvent did not attach to the product.…”
Section: Introductionmentioning
confidence: 99%